THE AMBER BRANCH OF UKRAINE: THE ISSUE OF DEVELOPING THE NATIONAL DEVELOPMENT PROGRAM - Komliev, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
In recent years, one of the brands of Ukraine has been amber. This is important for our country, because in the world the fashion for amber jewelry is preserved for centuries. Amber is constantly studied, all its new natural properties, consumer qualities are opened. Amber and products of its processing are now widely used in medicine, pharmaceuticals, perfumery, machine building, chemical, furniture, food improvement, food industry and agriculture. Worldwide the demand for amber raw materials is rising and so are the prices. Today, the industry is rapidly developing in Ukraine ("amber"), which includes the exploration, extraction and processing of amber. The development of the "amber" industry in Ukraine has caused a whole complex of interconnected problems. They (as well as the industry as a whole) are now the object of national security of the country. The only integrated national development program is one of them.The legislative basis for the development of the amber sphere is generally present in Ukraine, yet the matter of normativelegal has not been finalized yet. The main issue in the development of the amber sphere in Ukraine is the limitation of the basis of raw materials. In spite of the great demand and potentially great stock, Ukraine is not ready to access the world markets ascertain significant income in foreign currency. The broadening of the raw material base in the amber sphere is currently ongoing in Ukraine by extraction in the already known sources and the opening of new ones. The second way is the strategic one which will determine the development of the amber sphere for the years to come. Its basis should be formed by the forecast searching system of amber, the systematic methodology and comprehensive methods of research.
Keywords: amber, the amber sphere of Ukraine, the national program of development, the forecast searching system of amber, the normative-legal regulations